Isolation and Molecular Profiling Of Thermoresistant Bacteria From Chimneys Of Baking Industries Of Madurai, Tamilnadu, India: Life Sciences-Zoology for Better Disease Understanding - V.Parthasarathy; R. Babu Rajendran (International Journal of Life Science and Pharma Research, 2022)
The present study was chosen to discover the thermophiles isolation from chimneys of baking industries o Madurai, Tamilnadu, India. An attempt has been made to unearth the conserved sequences among them. Phylogenetic neighbour joining tree based on their 16S rRNA showing a relationship with related organisms has been constructed for each isolates keeping a species as an outgroup. In Madurai, baking industries have been found to be one of the hottest area having temperature as high as 120°C. Incubations of the bacterial colonies were done with covered water bath incubator at 70°C for 72-96 hrs in Castenholz TYE broth. The temperature range of 40-100°C, pH range of 4.0-10.0 and incubation period of 24-144 hrs was investigated for the best growth of thermophilic bacteria. Samples were collected in sterilized screw capped vials from different sites of Madurai Baking Industries and brought to the laboratory and kept at 4°C in the refrigerator till further processing. PCR products were sequenced using same primers by a commercial sequencing facility (Xcleris lab). The sequences of these ten bacterial isolates after sequencing were blasted using online NCBI BLAST program. Ten thermotolerant bacteria isolates were isolated and the optimal temperature for growth of the isolates was 70°C and the optimal pH was 7.0. 16S rRNA gene sequences of all these thermophilic bacterial isolates exhibited 98-99% homology with Bacillus sp. The phylogenetic analysis of the 16S rRNA gene sequences also confirmed the relationship of these thermophilic isolates with the genus Bacillus The 16S rRNA gene of all isolates was amplified, sequenced, and insilico analysis of these ten sequences was carried out. Based on BLAST alignment of 16S rRNA gene sequences of these isolates to GenBank sequences, these all isolates belonged to genus Bacillus and showed 98-99% similarity. The present study delves in to isolation, identification, characterisation,and analysis o the genomes of bacterial isolates such as Bacillus sp. VP1, Bacillus sp. VP2, Bacillus sp. VP3,Pseudomonas sp. VP4, Pseudomonas sp VP5,Bacillus licheniformis strain VP7,Bacillus sp. VP8, Bacillus sp. VP9, Bacillus altitudinis sp. VP10, and Bacillus cereus strain VP11.